Cleaning of Gas Emissions By Biological Method - Dyachok, Vasyl; Venher, Liubov; Huhlych, Serhiy; Svjantko, Iryna (Видавництво Львівської політехніки, 2022)
The paper shows the possibility of using chlorophyllsynthesizing microalgae of Chlorella Vulgaris to purify biogas from carbon dioxide (CO2), hydrogen sulfide (H2S) and ammonia (NH3). Experimental dependences of the dynamics of CO2 uptake by microalgae under the action of H2S inhibitor and NH3 activator are presented. A mathematical description of the growth of biomass of microalgae Chlorella Vulgaris depending on the concentration of hydrogen sulfide and ammonia was obtained. The optimal values of hydrogen sulfide and ammonia concentration for the efficient process of carbon dioxide uptake by chlorophyll-synthesizing microalgae Chlorella Vulgaris from biomethanization gas have been established.
Keywords: microalgae Chlorella Vulgaris; biogas; carbon dioxide (CO2); hydrogen sulfide (H2S); ammonia (NH3); nitrogen oxides (NxOy); sulfur dioxide (SO2)